Is talent development a matter of design or desire? - Wilkinson, S.; Ellis, LK. (The Sports Monograph, 2014)
There is a view that talent is something you are born with and it is in your genes; Lykken (1982, 1998) and Lykken et al. (1992) call this idea Emergenic and Simonton (1999) adds that this genetic inheritance of talent allows an individual to perform to a remarkably high level. To some extent this may be true, as talent does seem to have an innate element to it. However, to get ahead in competitive sports requires an athlete to have avid faith in themselves; self-belief. This could be why athletes with mediocre physical talent but with immense inner-drive can sometimes go much further than an athlete with superior talent; they may be naturally gifted but lack determination. Some researchers, such as Gagné (1985) believe that talent is combination of factors including genes, the environment and sheer hard work. Consequently, Gagné, (1985:103) provided a more encompassing definition for talent, stating that, Talent is the advanced mastery of methodically developed skills or abilities as well as knowledge in at least one area that places the individual in the top tier amongst age peers who have been, or who are involved in that same area. More recent work from Gagné (1999a, 1999b, 2005) shows that he has stood by his initial definition, to explore what might make one person more predisposed towards, or talented to perform something better that others. Because the theory usefully lends itself to be critiqued from biological, psychological and sociological perspectives, it is used to structure this discussion. Without such research, thinking about sporting talent; where it may be derived from and how it might flourish, sports coaches could still believe that a Ferrari is simply a combination of steel, red paint and Italians and that if you have the basic ingredients, magic will just happen. This would be a mistake!